(untitled) (Journal of humanities and social sciences exploratio, 2025)
This paper takes two art songs from Zhang Rui’s art song collection The Joy of Snowflakes as examples to study and analyze the artistic characteristics and singing of Zhang Rui’s art songs. The two art songs "Lei Ci (Eulogy)" and "Su Su" possess unique charm, skillfully integrating poetry and music. Combining literature research and music score analysis, the author explores the creative background and artistic characteristics of "Lei Ci (Eulogy)" and "Su Su". Additionally, based on the author’s own understanding and experience in learning and singing these two works, a singing analysis is conducted. This study aims to provide suggestions or references for students who will learn these two works in the future.